QUALIFICATION OF CLOUD CONTRACTS - Drazdauskas, Stasys (Teisė, 2017)
Legal qualification of cloud contracts is increasingly becoming one of the questions analysed as part of different studies, scientific research, or legislative initiatives. Depending on the type of cloud contract, sometimes cloud contracts are proposed to be qualified as a lease, in other cases as a service contracts. Cloud service providers sometimes define their services as grant of a license. This article aims to verify the proposals on qualification of cloud contracts, first describing the characteristics of cloud contracts and then analysing their conformance to the qualifying features of different types of regulated contracts.